The power of innate: Behavioural attachment and neural activity in responses to natural and artificial objects in filial imprinting in chicks - Cherepov, A. B.; Tiunova, A. A.; Anokhin, K. V. (Frontiers in Physiology, 2022)
Newly hatched domestic chicks are known to orient preferentially toward naturalistic stimuli, resembling a conspecific. Here, we examined to what extent this behavioral preference can be transcended by an artificial imprinting stimulus in both short-term and long-term tests. We also compared the expression maps of the plasticity-associated c-fos gene in the brains of chicks imprinted to naturalistic (rotating stuffed jungle fowl) and artificial (rotating illuminated red box) stimuli. During training, the approach activity of chicks to a naturalistic object was always higher than that to an artificial object. However, the induction of c-fos mRNA was significantly higher in chicks imprinted to a box than to a fowl, especially in the intermediate medial mesopallium, hyperpallium apicale, arcopallium, and hippocampus. Initially, in the short-term test (10 min after the end of training), chicks had a higher preference for a red box than for a stuffed fowl. However, in the long-term test (24 h after imprinting), the response to an artificial object decreased to the level of preference for a naturalistic object. Our results thus show that despite the artificial object causing a stronger c-fos novelty response and higher behavioral attachment in the short term, this preference was less stable and fades away, being overtaken by a more stable innate predisposition to the naturalistic social object.